Blood pressure in Afghan male immigrants to Denmark. (27th May 2013) - Asmar, Ali; Bülow, Jens; Simonsen, Lene; Christensen, Niels J.; Frandsen, Erik; Norsk, Peter
Summary Purpose Immigration from a Third‐World society to a Western society can be associated with higher blood pressure and salt sensitivity. We therefore tested whether immigrants from Afghanistan to Denmark compared with non‐immigrant Danes exhibit a (i) higher 24‐h ambulatory blood pressure (24‐h ABP) and (ii) blunted renin response to a change in salt intake. Methods Twenty‐four‐hour ABP was measured in 40 men of Afghan (Afghans) and 40 men of Danish (Danes) origin. Each group was divided into young (20–30 years, n = 20) and middle aged (40–60 years, n = 20). A 3‐day low (70 mmol per 24‐h) and a 3‐day high (250 mmol per 24‐h) salt intake were in addition instituted in subgroups of the young groups (n = 18). Results Young and middle‐aged Afghans exhibited a lower 24‐h mean arterial pressure (24‐h MAP) than the same respective age groups of Danes (83 ± 1 versus 90 ± 1 mm Hg, P<0·05, and 89 ± 2 versus 100 ± 1 mm Hg, P<0·05). 24‐h ABP did not change in any of the young groups during increased salt intake, whereas the Danes exhibited a greater decrease in plasma renin activity (PRA) (P<0·05). Plasma noradrenaline (PNA) was significantly higher among the young Afghans. Conclusions Afghan immigrants to Denmark exhibit a lower 24‐h ABP than Danes. In young Afghans, PRA is less sensitive to changes in salt intake, while PNA is higher and may reflect their lower systolic blood pressure and/or arterial pulse pressure. Whether these hormonal differences can explain the lower 24‐h ABP in Afghans should be further explored.